Community Argumentations on the Role of Women in the Kenduri Sko Tradition in Belui Village - Putri, Auliana Nur; Ravico, Ravico; Fadil, Marjan (Universitas Islam Negeri Sumatera Utara, 2025)
This research aims to find out the community's opinion regarding the role of women in the Kenduri Sko tradition in Belui Village, Kerinci Regency. This research uses a quantitative type of research. The data collection survey method is carried out using questionnaires. The sample for this research is the people of Belui village, Kerinci Regency. The results of this research show that the overall community response is regarding the role of women in the Kenduri Sko tradition in Belui Village. The indicators used in the questionnaire are divided into 7, namely Kenduri Sko knowledge, knowledge of women's roles, implementation of Kenduri Sko , forms of the Kenduri Sko tradition, aims of the Kenduri Sko tradition, impact of the Kenduri Sko tradition, response to the Kenduri Sko tradition. Based on the results of obtaining opinions using a questionnaire, the highest indicator for the purpose of the Kenduri Sko tradition is 84.40%, this shows that the community agrees with the aim of the Kenduri Sko tradition to preserve cultural values and customs. and the lowest questionnaire response indicator for the Kenduri Sko tradition was 74.21%, this shows that people are doubtful about the role of women in the Kenduri Sko tradition. The role of women in this research plays an important role in organizing the Kenduri Sko event, both in terms of preparation and implementation of the Kenduri Sko event in Belui Village.